ANALISIS PENGARUH AKSES INTERNAL TERHADAP EFEKTIVITAS PROSES PEREKRUTAN KARYAWAN DI INDONESIA: SUATU KAJIAN LITERATUR - Dircia da Costa Ruing; Mardani Supranata (Journal of Innovation Research and Knowledge, 2025)
This study aims to examine the influence of internal access in the employee recruitment process on the effectiveness of human resource management in Indonesia. Internal access refers to recruitment strategies that involve promotion, rotation, or internal placement of existing employees to fill vacant positions. Using a literature review method, this research analyzes empirical findings and relevant management theories from scholarly articles published from 2010 onward. The results indicate that internal access has a positive impact on employee performance, work motivation, and recruitment efficiency. The success of internal recruitment implementation is highly influenced by the principles of meritocracy, procedural justice, and the support of digital-based human resource information systems (HRIS). However, challenges such as selection bias, lack of transparency, and competency mismatches remain significant barriers. Therefore, organizations need to design internal recruitment systems that are competence-based, transparent, and digitally integrated. This study offers strategic implications for companies and opens avenues for further empirical and contextual research, particularly in strategic sectors within Indonesia